Efficiency of Processing of Secondary Raw Materials - U.K. Kasimov; R.I. Karimov (Zien Journals, 2022)
This article discusses polymer wastes that cause serious damage to the environment and their effective use. Secondary raw materials can be used as a starting material from polymer waste. During the writing of the article, attention was paid to the detection of harmful values of secondary raw materials, analysis of the use of secondary raw materials and the use of secondary raw materials
Keywords: Household waste; industrial waste; organic matter